A Study of Global Solar Radiations Measurement in Java Island, Indonesia - Pachman, Ardhya Fadhila; Didane, Djamal Hissein; Wijianto, Wijianto; Al-Ghriybah, Mohanad; Nasir, Nurul Fitriah; Al-Alimi, Sami; Manshoor, Bukhari (2023)
Solar energy is well-known renewable energy that has been widely used nowadays. Given that Solar energy is green, inexhaustible, pollution-free and simple to use, it has received significant interest all over the world including in Indonesia. Therefore, the main purpose of the present study is to evaluate and compare the potential of solar energy in six stations on Java Island in Indonesia. The methodology has used the renowned Angstrom-Prescott mathematical method while estimating the global solar radiation in the six stations on java island as a potential to utilize solar energy to be a source of electricity generation. The meteorological data used in this assessment is recorded in daily format for five consecutive years starting from 2015 until 2019. The results show that the area that has the highest global solar radiation potential is Banten city with an average value of 5.43 kWh/m2 while the city with the lowest global solar radiation potential is Yogya city with an average value of only 5.40 kWh/m2 . The highest clearness index value among the six provinces is in Jeteng with a value of 0.52 and the lowest is in the province of Jabar with a value of 0.50. Whereas the difference in the daily ratio of the duration of sunlight between one province and another province is very small. Moreover, each province has extraterrestrial solar radiation values increasing from January until June and then decreasing from July until December. Thus, in this study, it is expected that it can raise awareness to reduce conventional energy by utilizing domestic renewable energy.